Veridical mapping in savant abilities, absolute pitch, and synesthesia: an autism case study - Bouvet, Lucie; Donnadieu, Sophie; Valdois, Sylviane; Caron, Chantal; Dawson, Michelle; Mottron, Laurent (Frontiers in Psychology, 2014)
An enhanced role and autonomy of perception are prominent in autism. Furthermore, savant abilities, absolute pitch, and synesthesia are all more commonly found in autistic individuals than in the typical population. The mechanism of veridical mapping has been proposed to account for how enhanced perception in autism leads to the high prevalence of these three phenomena and their structural similarity. Veridical mapping entails functional rededication of perceptual brain regions to higher order cognitive operations, allowing the enhanced detection and memorization of isomorphisms between perceptual and non-perceptual structures across multiple scales. In this paper, we present FC, an autistic individual who possesses several savant abilities in addition to both absolute pitch and synesthesia-like associations. The co-occurrence in FC of abilities, some of them rare, which share the same structure, as well as FC’s own accounts of their development, together suggest the importance of veridical mapping in the atypical range and nature of abilities displayed by autistic people.